(untitled) (International Journal of Scientific Pediatrics, 2023)
Annotation. Obstructive bronchitis in children represents a serious medical and social problem, since they occupy one of the first places among the causes of childhood diseases. Despite many studies, the problem of obstructive bronchitis in frequently ill children remains not fully resolved, which is associated with the difficulty of timely diagnosis, peculiarities of clinical manifestations and laboratory data. The purpose of the scientific research is to study the state of cellular immunity in patients with obstructive bronchitis. Materials and research methods: to establish the relationship with indicators of cellular immunity, 80 patients with obstructive bronchitis were examined, divided into 2 groups: Group I - 40 patients with obstructive bronchitis, Group II - 40 patients with obstructive bronchitis in frequently ill children. Results: The results of the immunological study indicated disturbances in the T-cell immunity, expressed in a decrease in CD3, CD4, and a tendency towards a decrease in CD8, indicating the presence of a secondary immunodeficiency state in patients, possibly due to frequent respiratory diseases. The most informative indicators of the risk of a pathogenetically unfavorable increase in the cellular immune response in AOB are a decrease in the CD3+, CD4+, CD8+ subpopulation. Conclusions. This study allows us to better understand the pathogenetic role of the immune status in the development of obstructive bronchitis in children, for use in clinical practice and the development of more effective methods for diagnosing, prognosis and treatment of the disease.